Influencer the power to change anything - Patterson, Kerry, 1946- (New York : McGraw-Hill, 2008)
'Everyone wants to be an influencer. We all want to learn how to help ourselves and others change behavior. And yet, in spite of the fact that we routinely attempt to do everything from lose weight to improve quality at work, few of us have more than one or two ideas about how to exert influence. For the first time, Influencer brings together the breakthrough strategies of contemporary influence masters. By drawing from the skills of hundreds of successful influencers and combining them with five decades of the best social science research, Influencer shares eight powerful principles for changing behaviors -- principles almost anyone can apply to change almost anything.' ... From publisher's description.
You're an influencer -- Find vital behaviors -- Change the way you change minds -- Make the undesirable desirable : personal motivation -- Surpass your limits : personal ability -- Harness peer pressure : social motivation -- Find strength in numbers : social ability -- Design rewards and demand accountability : structural motivation -- Change the environment : structural ability -- Become an influencer.
Title from eBook information screen.
Includes bibliographical references and index.
Keywords: Influence (Psychology); Leadership; Power (Psychology); Social behavior; Psychology -- Popular Works; Einfluss; Macht; Sozialverhalten; Electronic books